Inpatient Institutional Care: The Forced Social Environment - Joyes, Emma C.; Jordan, Melanie; Winship, Gary; Crawford, Paul (Frontiers in Psychology, 2021)
The landscape of mental health recovery is changing; there have been calls for a shift from the clinical expertise being the dominant voice within mental healthcare towards a more personalised and collaborative service that supports those in need of mental healthcare to define what recovery is for the individual. Within this new recovery movement, there has been a recognition of the importance of the social environment in which individuals are situated and the relationship of this to mental health and wellbeing. Included in this is the importance of an individual’s role within society and the ways in which knowledge, such as experts by experience, can hold an important value. The argument then, is that social connectedness forms part of the recovery journey and that relationships can help us develop or re-connect with who we are in powerful ways. Such a view has only been strengthened by the recent and ongoing global Covid-19 pandemic. Within the UK, discussions of the importance of our wellbeing have become commonplace within the context of restricted social contact. With this heightened awareness of how the social contributes to wellbeing, it is important to consider the environments in which those in receipt of mental healthcare are situated. One of which is institutionalised care, where it is commonplace to restrict social contact. For example, by virtue of being within a locked environment, individuals’ freedom of movement is often non-existent and thus contacts with those not residing or working within the institution is restricted. Whilst such restrictions may be deemed necessary to protect the individual’s mental health, such environments can be unintentionally toxic. Data is presented from an ethnography that was conducted within an inpatient forensic mental health hospital in the UK to highlight the problematic social environment which some individuals experience. Key interpersonal issues are presented, such as, trust, racism, the threat of violence, and bullying that was experienced by staff and residents at the hospital. Consideration is given to the coping strategies enacted by residents and the pathologising of such behaviour. The consequences on interpersonal wellbeing are explored.